2018
DOI: 10.1007/s00125-018-4628-9
|View full text |Cite|
|
Sign up to set email alerts
|

Nuts as a replacement for carbohydrates in the diabetic diet: a reanalysis of a randomised controlled trial

Abstract: Aims/hypothesisIn line with current advice, we assessed the effect of replacing carbohydrate consumption with mixed nut consumption, as a source of unsaturated fat, on cardiovascular risk factors and HbA1c in type 2 diabetes. The data presented here are from a paper that was retracted at the authors’ request (10.2337/dc16-rt02) owing to lack of adjustment for repeated measures in the same individual. Our aim, therefore, was to fix the error and add new complementary data of interest, including information on c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…For that reason, several antioxidants (e.g., polyphenols) and vitamins, that are present in nuts, have been suggested to be effective treatments for ED and at the same time are beneficial for the cardiovascular system [38]. Previous studies reported that chronic consumption of nuts has proven effective for lowering LDL cholesterol [32] and improving glucose metabolism [39], among other cardiovascular risk factors, decreasing the incidence of major cardiovascular events [17]. Therefore, we strongly believe in the necessity to develop similar trials with participants at high cardiovascular risk and erectile dysfunction to accurately establish an effect of nut consumption on erectile function and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, several antioxidants (e.g., polyphenols) and vitamins, that are present in nuts, have been suggested to be effective treatments for ED and at the same time are beneficial for the cardiovascular system [38]. Previous studies reported that chronic consumption of nuts has proven effective for lowering LDL cholesterol [32] and improving glucose metabolism [39], among other cardiovascular risk factors, decreasing the incidence of major cardiovascular events [17]. Therefore, we strongly believe in the necessity to develop similar trials with participants at high cardiovascular risk and erectile dysfunction to accurately establish an effect of nut consumption on erectile function and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of tree nut and peanut consumption on lipid profiles from intervention studies published in the last ten years [31,32,33,34,35,36,37,38,39,40,41,42,43] are summarized in Table 2. The results of these clinical trials in a middle-aged population indicate a causal association between higher nut intake and lower levels of total cholesterol (T-C), low density lipoprotein-cholesterol (LDL-C), non-high density lipoprotein-cholesterol (non-HDL-C), triglycerides (TG), and apolipoprotein B (apoB), all markers of CV morbidity and mortality.…”
Section: Association Between Nut Consumption and Cardiometabolic Dmentioning
confidence: 99%
“…A new trial confirmed that, compared to a carbohydrate control diet, adding 75 g per day of mixed nuts (tree nuts and peanuts) to healthy diets could significantly lower small LDL-C ( p = 0.018), with a trend towards reduction for T-C ( p = 0.066) and non-HDL-C ( p = 0.067) in T2DM elderly patients [42].…”
Section: Association Between Nut Consumption and Cardiometabolic Dmentioning
confidence: 99%
See 2 more Smart Citations